Patient perspectives on current and potential therapies and clinical trial approaches for cocaine use disorder - Maahs, Suzanne; Leclair, Denise; Gomez-Mancilla, Baltazar; Kiluk, Brian D.; Muthusamy, Velusamy Shanmuganathan; Banerjee, Partha S.; Dasgupta, Shyamashree; Waye, Katherine M. (Frontiers in Psychiatry, 2024)
Cocaine use disorder (CUD) is characterized by continued use of cocaine despite serious impacts on life. The present study focused on understanding the perspective of individuals with current CUD, those in CUD remission and their supporters (defined as a friend or family member of someone who regularly used cocaine) regarding current therapies, future therapies, and views on clinical trials for CUD. Currently, there are no approved pharmacological therapies for CUD. Time, stigma, privacy, and cost are major barriers to seeking treatment. The new therapies/clinical trials are paramount but concerns over relapse and privacy. Focus on reduction of cravings and withdrawal to achieve long-term abstinence.Ideal treatment is combination of economic pharmacological and psychosocial therapy. This study can help inform the design of clinical trials and emphasizes the need for effective, safe and accessible therapies.